2022
DOI: 10.3390/children9091364
|View full text |Cite
|
Sign up to set email alerts
|

Minority Stress and Positive Identity Aspects in Members of LGBTQ+ Parent Families: Literature Review and a Study Protocol for a Mixed-Methods Evidence Synthesis

Abstract: Background: Parents and children in LGBTQ+ parent families face unique stressors (i.e., minority stress), but also possess unique resources (i.e., positive identity aspects) related to their family identity. Empirical evidence and theory suggest that these minority stressors and positive identity aspects are situated on the individual, couple, and family level and may be associated with key outcomes, including parent and child health, family functioning, and school-related outcomes. A systematic evidence synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 164 publications
1
16
1
Order By: Relevance
“…This echoes and extends other work showing that individuals from minoritized backgrounds may consider the potential impacts on family (e.g., scrutiny, shame) in deciding whether to disclose stigmatizing information (e.g., as in the case of Latinx women disclosing a history of childhood sexual abuse by family members; Castaneda, 2021). Further, even when participants noted complex feelings about their childhoods or parents, they embraced their parents and cherished the advantages that growing up with queer parents had bestowed on them, underscoring the power of queer family resilience (Farr et al, 2022; Siegel et al, 2022). In our view, the participants held the “both/and” of their experience, acknowledging the challenges associated with growing up with LGBTQ parents who were sometimes dealing with mental health and other issues, while also voicing gratitude for them and compassion for their struggles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This echoes and extends other work showing that individuals from minoritized backgrounds may consider the potential impacts on family (e.g., scrutiny, shame) in deciding whether to disclose stigmatizing information (e.g., as in the case of Latinx women disclosing a history of childhood sexual abuse by family members; Castaneda, 2021). Further, even when participants noted complex feelings about their childhoods or parents, they embraced their parents and cherished the advantages that growing up with queer parents had bestowed on them, underscoring the power of queer family resilience (Farr et al, 2022; Siegel et al, 2022). In our view, the participants held the “both/and” of their experience, acknowledging the challenges associated with growing up with LGBTQ parents who were sometimes dealing with mental health and other issues, while also voicing gratitude for them and compassion for their struggles.…”
Section: Discussionmentioning
confidence: 99%
“…They are vulnerable to social stigma related to their parents' sexual orientation and gender identity, as well as their family structure (e.g., formed via adoption or reproductive technologies, and/or characterized by the absence of a father or a mother). Depending on the degree to which their immediate and broader social environment is accepting versus rejecting of LGBTQ people, as well as their parents' own level of self‐acceptance and outness, they may be at risk for internalizing this social stigma (Fairtlough, 2008; Garner, 2004; Goldberg, 2007a; Robitaille & Saint‐Jacques, 2009; Siegel et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Burgeoning evidence and theory have documented the implications of parental well-being for interparental relationships, family functioning, parenting, and child adjustment (e.g., Feinberg, 2003;Goodman, 2020;van Santvoort et al, 2015). Theory-guided research on the well-being of LGBTQ+ parents specifically must also consider the implications of their experiences as minoritized individuals within minoritized relationships (Hammack et al, 2019;LeBlanc et al, 2015) and minoritized families (Fish & Russell, 2018;Siegel, Legler, et al, 2022). Critically, comparative investigations necessarily compared processes that are similar across heterosexual cisgender and LGBTQ+ parent family contexts, thus LGBTQ+ minorityspecific processes and experiences may have often been overlooked (Farr et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For mental health professionals working with families who are confronted with homophobic stigmatization, it is important to understand why some offspring in SMP families are resilient in the face of family stressors, while others are not [ 24 , 25 , 26 , 27 ]. Cross-sectional studies carried out in the U.S. and the Netherlands found that attending schools with lesbian, gay, bisexual, and transgender curricula, having lesbian parents who participated in the lesbian community, and having frequent contact with other offspring of SMPs protected children against the negative influences of stigmatization [ 11 , 20 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%